Effect of Yoga on Body and Mind Healing – A Systemaic Review - Khan, Parwej Alam Khan; Chugh, Karan; Kumari, Riyanka; Bhambu, Sudesh Kumar (International Research Journal of Ayurveda & Yoga, 2025)
Yoga is an ancient holistic practice that integrates physical movement, breath control, meditation, and ethical principles to promote overall well-being. In recent years, yoga has gained significant recognition for its therapeutic benefits on mental health. This paper explores the role of yoga in mind healing, emphasizing its ability to reduce stress, anxiety, depression, and emotional imbalances. Scientific studies demonstrate that yoga stimulates the parasympathetic nervous system, increases levels of neurotransmitters such as GABA and serotonin, and enhances mindfulness and self-awareness. Key components such as asanas (postures), breathing techniques, and meditation contribute to emotional regulation, improved sleep, and cognitive clarity. Yoga also supports trauma recovery and resilience by fostering a safe, introspective space for healing.